Challenges in linking health research to policy: a commentary on developing a multi-stakeholder response to orphans and vulnerable children in Ghana - Anakwah Kwadwo; Selby Richmond; Gyapong John (BMC, 2011)
Abstract The Research and Development Division (RDD) of the Ghana Health Service (GHS) has a remit to build research capacity and conduct policy relevant research. By being situated within the GHS, RDD has good access to directors and programme managers, within and beyond the Ministry of Health. This structure has been facilitating collaboration through research cycles for 20 years, from agenda setting to discussions on policy relevance. This approach has been applied to research activities within the Addressing the Balance of Burden in AIDS (ABBA) Research Programme Consortium to tackle the challenges facing HIV affected orphans and vulnerable children (OVCs). The government strategy on OVCs recommends they should be encouraged to live in their home communities rather than in institutions. We present lessons here on efforts to use research to build a response across different agencies to address the problems that communities and families face in caring for these children in their communities. This approach to building consensus on research priorities points to the value of collaboration and dialogue with multiple stakeholders as a means of fostering ownership of a research process and supporting the relevance of research to different groups. Our experience has shown that if the context within which researchers, policy makers and stakeholders work were better understood, the links between them were improved and research were communicated more effectively, then better policy making which links across different sectors may follow. At the same time, collaboration among these different stakeholders to ensure that research meets social needs, must also satisfy the requirements of scientific rigour.